Mathematics Anxiety Level of Pre-Service Elementary School Teachers During Online Learning in the Covid-19 Pandemic - Imanuel Yosafat Hadi Manapa (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
The purpose of this study was to find out students' math anxiety levels and compare math anxiety levels between semesters. This research was conducted because of the impact of online lectures during the pandemic era, namely the decrease in student achievement in all mathematics courses. This research was conducted in the Primary School Teacher Education Study Program of Tribuana Kalabahi University. The research method used is a quantitative research method with a comparative approach. The subjects of this study were 157 students who were in semesters 2 and 4. The instrument used in this study was the Revised-Mathematics Anxiety Survey (R-MAX) developed by Bursal and Paznokas. In this study, the instrument feasibility test is still conducted using the validity of the content and reliability test of the instrument. This instrument is declared valid in content according to mathematicians. In addition, the instrument is declared reliable using the Cronbach Alpha method with a reliability coefficient of 0.911. The results showed that students' math anxiety levels were at moderate levels. Cumulatively, 71.3% of students had moderate to very high anxiety disorders. Further comparative test results using independent t-tests showed that there was no difference in the average student math anxiety score based on semester class. Special attention is needed from the University considering the impact of student anxiety on learning achievements and pedagogic competencies in the future. Keywords: online learning, student math anxiety.